Anisotropies of solar energetic electrons in the MeV range measured with Solar Orbiter/EPD/HET - Fleth S; Kuehl P; Kollhoff A; Wimmer-Schweingruber RF; Heber B; Rodríguez-Pacheco J; Dresing N (EDP SCIENCES S A, 2025)
Aims. This study analyses relativistic electron measurements obtained by the High Energy Telescope (HET) aboard Solar Orbiter in the energy range from 200 keV to above 10 MeV. Caveats of these measurements are discussed. The purpose of this study is to analyse anisotropies of relativistic solar energetic electrons utilising the different viewing directions of HET.
Methods. We identified time periods of interest, that is, those with enhanced electron flux due to a significant solar component, and composed a list of these time periods, including additional observations such as maximum energy and flux as well as the first-order anistropy.
Results. This study provides an overview of HET measurements of MeV electrons and a list of time periods of enhanced flux of relativistic solar electrons, 21 in total. For the first time with Solar Orbiter/EPD/HET, the anisotropies of high-energy electrons have been measured. Specifically, we find three time periods with significant anisotropy above 1 MeV within 0.5 au.